2007
DOI: 10.1097/01.aud.0000249787.97957.5b
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Bone Oscillator Coupling Method, Placement Location, and Occlusion on Bone-Conduction Auditory Steady-State Responses in Infants

Abstract: Objective: The aim of these experiments was to investigate procedures used when estimating boneconduction thresholds in infants. The objectives were: (i) to investigate the variability in force applied using two common bone-oscillator coupling methods and to determine whether coupling method affects threshold estimation, (ii) to examine effects of bone-oscillator placement on bone-conduction ASSR thresholds, and (iii) to determine whether the occlusion effect is present in infants by comparing bone-conduction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
49
1
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(56 citation statements)
references
References 21 publications
5
49
1
1
Order By: Relevance
“…The results of the present study, in which 2.0-kHz tones were used (in order to avoid the complication of the occlusion effect in the occluded ears and of tactile sensation) with no difference in threshold, are thus in agreement with those of earlier reports with respect to the osseous sites [e.g. Small et al, 2007;Toll et al, 2011].…”
Section: Discussionsupporting
confidence: 81%
“…The results of the present study, in which 2.0-kHz tones were used (in order to avoid the complication of the occlusion effect in the occluded ears and of tactile sensation) with no difference in threshold, are thus in agreement with those of earlier reports with respect to the osseous sites [e.g. Small et al, 2007;Toll et al, 2011].…”
Section: Discussionsupporting
confidence: 81%
“…The implication appears to be that low frequency BC thresholds worsen, and high frequency BC thresholds improve, with maturation [13]. The second study assessed the effect of the bone-oscillator coupling method, location, and occlusion on BC ASSR in infants [14]. Results indicated that the coupling methods (elastic band vs. hand-held) do not render significantly different results.…”
Section: Introductionmentioning
confidence: 99%
“…Since the exact force of the headband was not measured, there may have been slight differences in exerted force across subjects. Coupling method, placement on temporal bone or mastoid, and the occlusion effect have not been found to exercise a significant effect on BC ASSR thresholds in infants [14]. The BC stimuli were calibrated in reference-equivalent threshold force levels (RETFLs) in dB re:1 mN corresponding to 0 dB HL for the mastoid [19], using a Larson Davis 824 sound level meter and artificial mastoid simulator.…”
Section: Ac and Bc Assrmentioning
confidence: 99%
See 1 more Smart Citation
“…This place was chosen to separate the electrode from the vibrator as far as possible so as to avoid stimulus artifacts at high presentation levels. A pilot study as well as the study of Small et al [18] showed that there was no significance difference in behavioral test results with the vibrator placed either at the mastoid or higher on the temporal bone. The measurements at each frequency, both in the single-and multiple-stimulus conditions, started at 50 dB nHL and were then decreased in 5-dB steps.…”
Section: Test Proceduresmentioning
confidence: 99%